2020
DOI: 10.20944/preprints202007.0618.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Training of Primary Chicken Monocytes Results in Enhanced Pro-inflammatory Responses

Abstract: Beta-glucan-stimulated mammalian macrophages show an increased responsiveness to secondary stimulation in a nonspecific manner. This phenomenon is known as trained innate immunity. Our study aimed to explore training of primary chicken monocytes. We hypothesized that primary chicken monocytes, similar to their mammalian counterparts, can be trained with β-glucan resulting in increased responses of these cells to a secondary stimulus. Primary blood monocytes of white leghorn chickens were primary stimu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Simultaneously, the expression of major histocompatibility complex (MHC) class II and CD40, indicating immunological activation, was also upregulated [85]. These results indicate…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 79%
See 1 more Smart Citation
“…Simultaneously, the expression of major histocompatibility complex (MHC) class II and CD40, indicating immunological activation, was also upregulated [85]. These results indicate…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 79%
“…Chicken primary monocytes treated with β-glucan exhibited increased production of nitric oxide compared with cells treated with LPS. Simultaneously, the expression of major histocompatibility complex class II and CD40, indicating immunological activation, was also upregulated [ 85 ]. These results indicate that β-glucan can drive the immune system to better deal with invading foreign substances, although further mechanistic studies using in vivo models are necessary to validate metabolic and epigenetic modulations.…”
Section: Antibiotics and Their Substitutementioning
confidence: 99%
“…In recent years much attention has been paid to this concept of trained innate immunity. Studies in a broad variety of animal species, including mammals, birds and fish, have shown that the innate immune system can be trained, indicating the conserved nature of this immune mechanism (30)(31)(32). Trained innate immunity is defined as the activation of the innate immune system resulting in a memory-like enhanced responsiveness to subsequent triggers driven by epigenetic mechanisms and metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%